Teaching mid‐urethral sling surgery to residents: Impact on operative time and postoperative outcomes. Issue 8 (31st March 2017) - Sharif‐Afshar, Ali‐Reza; Wood, Lauren N.; Bresee, Catherine; Souders, Colby P.; Gross, Bruno S.; Shkolyar, Eugene; Anger, Jennifer T.; Eilber, Karyn S.
Abstract : Aims: The purpose of this study was to determine the impact of resident teaching on outcomes of mid‐urethral sling surgery. Methods: A retrospective review of female patients who underwent an outpatient transobturator (TOT) synthetic mid‐urethral sling procedure with and without concomitant prolapse repair by two surgeons (JA, KE) in a tertiary female pelvic medicine practice was performed. Total procedure time (TPT = time from incision to closure including sling placement and any prolapse procedure), estimated blood loss (EBL), and postoperative complications including urinary retention, mesh exposure, reoperation, vaginal bleeding, and leg pain were compared between cases with and without the presence of a resident. Results: One hundred thirty‐four women underwent an outpatient transobturator sling procedure. Fifty‐seven patients (43%) had a concomitant prolapse procedure. A resident was present at 57% (76/134) of cases. The average observed TPT (±SEM) was 60.6 ± 3.1 min when a resident was present and 46.6 ± 2.5 min when a resident was not present ( P  = 0.001). However, residents were more likely to be present when concomitant procedures were performed ( P  = 0.003). After adjusting for this, the presence of a resident increased TPT by an estimated 7.9 ± 2.5 min ( P  = 0.002). There was no statistical difference in EBL or postoperative complications. Conclusions: Resident participation in transobturator sling procedures resulted in a statistically significant, although clinically small, increase in operative time and had no significant impact on EBL or postoperative complications.